What is Islamophobia? Disentangling Citizens' Feelings Toward Ethnicity, Religion and Religiosity Using a Survey Experiment - Marc Helbling; Richard Traunmüller (British Journal of Political Science, 2020)
What citizens think about Muslim immigrants has important implications for some of the most pressing challenges facing Western democracies. To advance contemporary understanding of what `Islamophobia' really is – for example, whether it is a dislike based on immigrants' ethnic background, religious identity or specific religious behaviors – this study fielded a representative online survey experiment in the UK in summer 2015. The results suggest that Muslim immigrants are not per se viewed more negatively than Christian immigrants. Instead, the study finds evidence that citizens' uneasiness with Muslim immigration is first and foremost the result of a rejection of fundamentalist forms of religiosity. This suggests that common explanations, which are based on simple dichotomies between liberal supporters and conservative critics of immigration, need to be re-evaluated. While the politically left and culturally liberal have more positive attitudes toward immigrants than right-leaning individuals and conservatives, they are also far more critical of religious groups. The study concludes that a large part of the current political controversy over Muslim immigration is related to this double opposition: it is less about immigrants versus natives or even Muslim versus Christians than about political liberalism versus religious fundamentalism.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.; doi: 10.7910/DVN/L2OZPI
Keywords: 330; Islamophobia; ethnicity; religion; religiosity; liberalism; immigration